ISOLASI, IDENTIFIKASI, DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA GOLONGAN TRITERPENOID PADA RIMPANG TEMU PUTIH (Curcuma zedoaria (Berg.) Roscoe) - Susanah Rita, Wiwik (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
Isolation, identification, and antibacterial activity examination of triterpenoid compounds from rhizome of Curcuma zedoaria (Berg.) Roscoe have been conducted. Maseration of 600 g dry powder of those rhizome using nhexane and ethanol respectively yielded 9,79 g of n-hexane extract and 23,45 g of ethanol extract. The ethanol extract containing triterpenoids was dissolved into ethanol-water (7:3) mixture. The mixture was evaporated to remove the ethanol and then partitioned by chloroform. Hence, two extract were produced i.e., chloroform and water extract. The n-hexane and chloroform extracts obtained contained triterpenoids based on fitochemical test of Lieberman-Burchard. Antibacterial test showed that only chloroform extract was active with inhibition zone of 2 mm for Staphylococcus aureus. Compound separation of the chloroform extract using column chromatography produced 0,44 g brown isolate which contained triterpenoids (fraction F1). The isolate inhibited the growth of Staphylococcus aureus and Escherichia coli with weak inhibition zone at 500 ppm and 1000 ppm. Infrared spectra indicated that the isolate was a carboxylic acids triterpenoids, with characteristic functional groups of –OH bonded, –CH, C=O of carboxylic acids, –C=C, –CH2, –CH3, and C–O alcohol. The ultraviolet-visible spectra showed maximum absorption at 242 nm and 280 nm.
Keywords: Curcuma zedoaria (Berg.) Roscoe, triterpenoids, Staphylococcus aureus, Escherichia coli